2005
DOI: 10.1093/protein/gzi007
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive IL7-diphtheria fusion toxin secreted by mammalian cells

Abstract: A number of targeted cytotoxic agents have been developed that selectively kill malignant or otherwise pathological cells. These engineered proteins consist of a potent cytotoxic element connected to a ligand domain that binds to specific molecules on the surface of the target cell. Several of these agents have shown promise in clinical trials and one is currently administered to patients. A significant technical obstacle that has impeded the development of some of these toxins is the difficulty of preparing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this study, we proposed that stem cell delivery of PE‐cytotoxins could circumvent current limitations by allowing the continuous release of therapeutic agent. Previous studies have demonstrated that a mutant form of EF‐2 confers resistance to EF‐2‐ADP‐ribosylating toxins , and that mammalian cells can be modified to secrete diphtheria‐fused toxin . We used a similar strategy to engineer a toxin‐resistant stem cell line able to stably secrete PE‐cytotoxins using single‐stranded oligonucleotides encoding mutant EF‐2 to convert endogenous EF‐2 into a toxin‐resistant variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we proposed that stem cell delivery of PE‐cytotoxins could circumvent current limitations by allowing the continuous release of therapeutic agent. Previous studies have demonstrated that a mutant form of EF‐2 confers resistance to EF‐2‐ADP‐ribosylating toxins , and that mammalian cells can be modified to secrete diphtheria‐fused toxin . We used a similar strategy to engineer a toxin‐resistant stem cell line able to stably secrete PE‐cytotoxins using single‐stranded oligonucleotides encoding mutant EF‐2 to convert endogenous EF‐2 into a toxin‐resistant variant.…”
Section: Discussionmentioning
confidence: 99%
“…Established human GBM lines U87, LN229, U251, Gli36vIII and primary GBM4, GBM6, GBM23, GBM64, and BT74 cells were grown as described previously . 293DT cells were cultured as previously described . Melanoma and breast cancer cell lines were grown as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…This line is particularly suitable for transient expression assays because it is readily transfected at high efficiency, and the SV40 T antigen replicates plasmids containing the SV40 origin. In work published in 2005 [ 43 ], this cell line was mutated, and clones that were highly resistant to DT were isolated and used to express DAB389-IL7, a very potent fusion toxin composed of the catalytic and transmembrane domains of diphtheria toxin fused to interleukin 7.…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…Until recently, major factors limiting the therapeutic use of plant and animal toxins were the difficulty and high cost of bulk extraction or large‐scale chemical synthesis. Now, instead of the labour‐intensive process of purifying toxins directly from their original source, an increasing number can be produced in large quantities through the cloning and expression of toxin genes in bacteria, yeast or cultured cells (Ducancel et al , 1989; Shulga‐Morskoy & Rich, 2005). To facilitate their manufacture, protein toxins can also be truncated to the minimum size that is required for functional activity.…”
mentioning
confidence: 99%